The role of clinical guidelines in reducing the burden of cardiovascular diseases. - R. V. Polibin; I. V. Petukhova (Фундаментальная и клиническая медицина)
Aim. To assess the impact of implementing evidencebased cardiology guidelines into the clinical practice in the Russian Federation and selected European countries on trends in cardiovascular disease (CVD) mortality. Materials and Methods. Mortality data were obtained from the Global Burden of Disease database. Countries were grouped into five clusters based on CVD mortality rates. Information on implemented clinical guidelines was gathered from professional society websites and published national and international sources. We further conduced an epidemiological analysis of CVD mortality before and after the implementation of clinical guidelines, including before-after analysis of mortality trends. Results. After the implementation of clinical cardiology guidelines, a reduction in CVD mortality was observed in Spain, Estonia, Russia, Latvia, Belarus, Ukraine, and especially United Kingdom and the Netherlands. Decrease in mortality in Belgium, France, Slovakia, Italy, Portugal, Germany, and the Czech Republic was associated with successful CVD prevention campaigns and active use of clinical cardiology guidelines in clinical practice. Increased mortality in Croatia, Serbia, Bosnia and Herzegovina, Lithuania, Romania, and Bulgaria was linked to limited economic resources that hindered full implementation of preventive and treatment programs. Conclusion. The integration of CVD clinical guidelines into the national healthcare systems has played a significant role in reducing mortality. Achieving the full potential of CG implementation requires a comprehensive strategy that ensures access to quality care for the entire population, including preventive and rehabilitation programs, sufficient funding, modern infrastructure, and continuous professional development of healthcare personnel. Systemic integration of guideline-based prevention, diagnostics, and treatment can further reduce CVD morbidity and mortality